Elizabeth Burt papers - Burt, Elizabeth, 1839-; Burt, Andrew, 1771?-1817.; Burt, Andrew Gano, 1810-1875.; Burt, Andrew, 1839-1915.
Typescript of Burt's autobiographical account, "An Army Wife's Forty Years in the Service, 1862-1902," and letters to her daughter, Edith Burt, discussing family matters and describing the routines of military post life at Fort Bidwell, Calif.; Forts Bridger, Laramie, D. A. Russell, Sanders, and Washakie, Wyo.; Forts Missoula and C. F. Smith, Mont.; Forts Omaha and Robinson, Neb., and elsewhere. Subjects include relations with the Indians, particularly Shoshone Chief Washakie, and social events and meetings with Mark Twain and Owen Wister. Includes correspondence, diaries, and other papers of Burt's husband Andrew Burt, her father-in-law Andrew Gano Burt, and Andrew Burt.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, positive photocopies and typewritten transcripts.
Collection material in English.
Keywords: Burt, Edith -- Correspondence; Twain, Mark, -- 1835-1910.; Washakie, -- Shoshoni chief, -- -1900.; Wister, Owen, -- 1860-1938.; United States. -- Army; Burt family; Army spouses -- United States; Fortification -- California; Fortification -- Montana; Fortification -- Nebraska; Fortification -- Wyoming; Indians of North America -- Government relations; Military bases -- California; Military bases -- Montana; Military bases -- Nebraska; Military bases -- Wyoming; Shoshoni Indians; Fort Bidwell (Calif.); Fort Bridger (Wyo.); Fort C. F. Smith (Mont.); Fort D. A. Russell (Wyo.); Fort Laramie (Wyo.); Fort Missoula (Mont.); Fort Omaha (Neb.); Fort Robinson (Neb.); Fort Sanders (Wyo.); Fort Washakie (Wyo.)